Internalisasi Nilai Huyula dan Eya Dila Pito’pito’o dalam Pendidikan Asuransi Syariah - Mohamad Anwar Thalib (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study is motivated by the low level of trust among the younger generation in Islamic financial institutions, particularly Islamic insurance, which remains less familiar than conventional insurance. The research aims to integrate Gorontalo’s local cultural values into Islamic insurance education to enhance young people’s understanding and confidence in Sharia-based risk protection systems. Using a qualitative descriptive approach, data were collected through in-depth interviews with four alumni of the Sharia Accounting Study Program at IAIN Sultan Amai Gorontalo who had recently entered the workforce. Informants were selected using purposive sampling to align with the study’s objectives. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that although students possess theoretical knowledge of Islamic insurance, they lack practical confidence due to limited information and the dominance of conventional insurance. Integrating the local value of Huyula (mutual cooperation) reinforces the understanding of the tabarru’ principle (mutual assistance), while Eya dila Pito’pito’o (God never closes His eyes) instills moral awareness and spiritual responsibility. These integrations make Islamic insurance learning more contextual, meaningful, and transformative. The study implies the need for culturally grounded Islamic economic education models to strengthen Sharia financial literacy and inclusion in the digital era.